2016
DOI: 10.1007/s00410-016-1269-1
|View full text |Cite
|
Sign up to set email alerts
|

Empirical calibration of the clinopyroxene–garnet magnesium isotope geothermometer and implications

Abstract: between clinopyroxene and garnet. The equilibrium Δ 26 Mg clinopyroxene-garnet and corresponding temperature data obtained in this study, together with those available so far in literatures for natural eclogites, are used to calibrate the clinopyroxene-garnet Mg isotope thermometer. This yields a function of Δ 26 Mg clinopyroxene-garnet = (0.99 ± 0.06) × 10 6 /T 2 , where T is temperature in Kelvin. The refined function not only provides the best empirically calibrated clinopyroxene-garnet Mg isotope thermomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 72 publications
4
12
1
Order By: Relevance
“…Taking all the mineral separates together, hornblende has higher δ 26 Mg values compared to chlorite (Figure 3), consistent with mineral separate data reported by Ryu et al (2011) but in contrast to Chapela Lara et al (2017) who observed that chlorite had higher δ 26 Mg values than both pyroxene (by ∼0.2 ) and amphibole (by ∼0.5 ), though they note that the amphiboles were heavily altered. Garnet had lower δ 26 Mg values compared to clinopyroxene (Figure 3), consistent with previous studies (Wang et al, 2012(Wang et al, , 2014Hu et al, 2016;Li et al, 2016). A large inter-mineral range is also observed in δ 7 Li values from +3.2 in chlorite (Ro4) to +12.1 in hornblende (Ro3 , Table 1).…”
Section: Rock and Mineral Separatessupporting
confidence: 90%
See 1 more Smart Citation
“…Taking all the mineral separates together, hornblende has higher δ 26 Mg values compared to chlorite (Figure 3), consistent with mineral separate data reported by Ryu et al (2011) but in contrast to Chapela Lara et al (2017) who observed that chlorite had higher δ 26 Mg values than both pyroxene (by ∼0.2 ) and amphibole (by ∼0.5 ), though they note that the amphiboles were heavily altered. Garnet had lower δ 26 Mg values compared to clinopyroxene (Figure 3), consistent with previous studies (Wang et al, 2012(Wang et al, , 2014Hu et al, 2016;Li et al, 2016). A large inter-mineral range is also observed in δ 7 Li values from +3.2 in chlorite (Ro4) to +12.1 in hornblende (Ro3 , Table 1).…”
Section: Rock and Mineral Separatessupporting
confidence: 90%
“…Research on the δ 26 Mg values of mineral separates has demonstrated variation in δ 26 Mg values which in some cases overlaps with the δ 26 Mg range in carbonate rocks (−5.57 to −0.38 , Teng, 2017), e.g., biotite (−0.40 to +0.44 , Shen et al, 2009;Ryu et al, 2011), chlorite (−1.82 to +0. 40 , Ryu et al, 2011;Pogge von Strandmann et al, 2015;Chapela Lara et al, 2017), clinopyroxene (−0.62 to +0.43 , Pogge von Strandmann et al, 2011;Wang et al, 2012Wang et al, , 2014Hu et al, 2016;Li et al, 2016;Chen et al, 2018;Stracke et al, 2018), and garnet (−1.96 to −0.37 , Wang et al, 2012Wang et al, , 2014Pogge von Strandmann et al, 2015;Hu et al, 2016;Li et al, 2016;Stracke et al, 2018). Within single rock samples, resolvable variation has also been observed e.g., 1.5 between chlorite and hornblende in granite (Ryu et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Garnet has a light Mg isotope composition compared to coexisting silicates (Li et al, 2011(Li et al, , 2016Wang et al, 2012Wang et al, , 2014Huang et al, 2013). The difference in Mg coordination between garnet (eight-fold) and most silicate minerals (sixfold) causes 24 Mg to be preferentially incorporated into garnet, leaving the surrounding minerals enriched in 26 Mg (Li et al, 2011, 2016; Wang et al, 2012Wang et al, , 2014Huang et al, 2013).…”
Section: Hypotheses For Mg Isotope Variationsmentioning
confidence: 99%
“…The difference in Mg coordination between garnet (eight-fold) and most silicate minerals (sixfold) causes 24 Mg to be preferentially incorporated into garnet, leaving the surrounding minerals enriched in 26 Mg (Li et al, 2011, 2016; Wang et al, 2012Wang et al, , 2014Huang et al, 2013). Both equilibrium and disequilibrium inter-mineral fractionation can occur between garnet and coexisting silicates (Li et al, 2016). Therefore, partial melting that leaves a garnet-rich residue could produce a melt with a relatively heavy Mg isotope composition.…”
Section: Hypotheses For Mg Isotope Variationsmentioning
confidence: 99%
“…The constant inter-mineral Mg isotope fractionation, together with homogeneous mineral chemistry and equilibrium oxygen isotopic partitioning between clinopyroxene and garnet, suggests an equilibrium Mg isotope fractionation (Li et al 2011). Later analyses of coexisting clinopyroxene and garnet in cratonic eclogites (Wang et al 2012(Wang et al , 2015 and orogenic eclogites (Wang et al 2014a, b;Li et al 2016) also found large equilibrium inter-mineral Mg isotope fractionation. This large equilibrium Mg isotope fractionation is controlled by different coordination numbers of Mg in these two minerals, with six in clinopyroxene and eight in garnet, as minerals with lower coordination number favoring heavier isotopes when thermodynamic equilibrium is achieved (Li et al 2011(Li et al , 2016Wang et al 2012Wang et al , 2015Huang et al 2013;Young et al 2015).…”
Section: Introductionmentioning
confidence: 97%